Icariin restrains NLRP3 inflammasome-mediated Th2 immune responses and ameliorates atopic dermatitis through modulating a novel lncRNA MALAT1/miR-124-3p axis - Wei Zhao; Huan-Huan Yu; Wei-Wei Meng; Ai-Min Liu; Bu-Xin Zhang; Ying Wang; Jie Li; Li Wang; Yu-Fu Fang (Taylor & Francis Group, 2023)
AbstractContext Atopic dermatitis (AD) is a common inflammatory skin disease characterized with hyperactivation of type 2 T helper (Th2) immune responses. Icariin is a flavonoid glucoside with anti-inflammatory activities, which has been used to treat multiple diseases.Objective The present study investigates the underlying mechanisms by which icariin regulates Th2 responses and AD development.Materials and methods BALB/c mice were induced by DNFB to establish AD models, and injected with or without 10 mg/kg icariin for 2 weeks (i.p., daily). CD4+T cells were induced by Th2 condition to simulate AD in vitro, and also treated with or without 100 µM icariin.Results Icariin ameliorated AD-like skin lesion, manifested as a significant decrease in dermatitis scores (from 8.00 ± 1.00 to 3.67 ± 0.58), serum IgE levels (from 3119.15 ± 241.81 to 948.55 ± 182.51 ng/mL), epidermal thickness (from 93.86 ± 4.61 to 42.67 ± 2.48 µm) and infiltration of mast cells (from 60.67 ± 3.21 cells to 36.00 ± 2.65 cells). Also, icariin inactivated NLRP3 inflammasome, inhibited Th2 skewing, reduced lncRNA MALAT1 expression, but elevated miR-124-3p expression in vivo and in vitro. MALAT1 increased NLRP3 expression through targeting miR-124-3p. Knockdown of MALAT1 repressed NLRP3 inflammasome activation and mitigated Th1/Th2 imbalance in Th2-conditioned CD4+T cells, whereas both MALAT1 overexpression and miR-124-3p inhibition ablated the inhibitory effects of icariin on Th2 immune responses.Discussion and conclusions The findings further improve our understanding of the mechanism by which icariin affects AD progression, and highlights the potential of icariin in the treatment of AD.